Mental wellbeing of healthcare workers working in quarantine centers during the COVID-19 pandemic in Qatar - Wadoo, Ovais (Qatar Med J, 2021)
Background: Healthcare workers managing Coronavirus 19 (COVID-19) patients are at increased risk of poor mental wellbeing. The available literature on the psychological impact in the Arabian Gulf region is limited, and a more in-depth analysis of factors affecting frontline healthcare workers’ mental wellbeing is warranted. The aim of this study was to evaluate and explore healthcare workers’ wellbeing working in quarantine centers in Qatar. Methods: This study was a cross-sectional, web-based survey conducted on healthcare workers managing patients in designated quarantine centers. Healthcare workers associated with 51 COVID-19 quarantine centers were eligible to participate in this survey from April 19 to May 3, 2020. The primary outcome of interest was mental wellbeing as measured by the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS). Results: A total of 127 of 169 contacted staff members completed the survey, with a participation rate of 75%. Approximately 17.4% of participants had well-being scores of less than 45, indicating suboptimal wellbeing and a high risk of psychological distress and depression. The multivariable logistic regression analysis showed that nurses are associated with increased risk (more than the fivefold higher risk of having WEMWBS score < 45) of adverse mental wellbeing (adjusted OR 5.65; 95% CI 0.57, 56.4; p = 0.140). Conclusion: The psychological impact of working in quarantine centers on healthcare workers was less than what has been reported globally. Nurses are the most vulnerable group. It is essential that health services monitor the psychological impact on its workforce and puts appropriate mitigation strategies in place.